Development Standard Operational Procedure of Safety Architecture Work in University of Indonesia Project Based on Work Breakdown Structure to Reduce Work Accidents - Alwan Muhammad Naufal; Ayu Herzanita Yufrizal; Yusuf Latief; Rossy Armyn Machfudiyanto (Journal of International Conference Proceedings (JICP), 2021)
The construction industry is one of the most dangerous industries in the world, due to its very high accident and death rate. As a high-risk construction industry, in addition to cost, time and quality, work safety will have a major impact on the success of a project. With the procedure safety properly, it is expected that work accidents will be reduced due to integrated work breakdown structure. The method used in this study is qualitative method, with research strategy in the form of archival analysis, case study, and expert validation. Data collection was conducted by interview method with questionnaires with professional experts who have long worked in the field of Safety, which then resulted in the conclusion that Standard Operational Procedures on Architectural work can reduce work accident.